2020
DOI: 10.1021/acs.jpcc.0c00943
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanisms of Zirconium-Containing Active Sites over the SBA-15 Zeolite Framework for Xylose Conversion to Methyl Lactate

Abstract: Zr-containing SBA-15 zeolite (Zr-SBA-15) catalysts show good catalytic performance toward xylose conversion to methyl lactate (ML). Here, we report our study on the catalytic mechanisms for the conversion of β-xylopyranose and methanol to ML, glycolaldehyde, and water (1) over modeled −(SiO)3Zr­(OH) ([Zr-1]) and −(SiO)2Zr­(OH)2 ([Zr-2]) active sites on Zr-SBA-15. The gross reaction (1) mainly involves two kinds of reaction stages, that is, aldose–ketose or ketose–aldose tautomerization and retro-aldol condensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The results show the highest MLA yield (47.4 %) for the Sn‐only catalysts, which is achieved over Sn‐Beta‐F, while the highest MVG yield (17.9 %) is reached over Sn‐Beta‐PS. It is well known that both MLA and MVG are derived from the C3 and C4 (C2) products produced by the retro‐aldol condensation of fructose and glucose, respectively, and subsequently obtained by similar chemical transformations (e.g., dehydration, keto‐enol tautomerization, 1,2‐hydride shift, and internal Cannizzaro reaction) [25] . Early work has shown that the formation of MVG from C4 sugars can be stimulated by catalytic sites in confined space and operating at higher temperature [26] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show the highest MLA yield (47.4 %) for the Sn‐only catalysts, which is achieved over Sn‐Beta‐F, while the highest MVG yield (17.9 %) is reached over Sn‐Beta‐PS. It is well known that both MLA and MVG are derived from the C3 and C4 (C2) products produced by the retro‐aldol condensation of fructose and glucose, respectively, and subsequently obtained by similar chemical transformations (e.g., dehydration, keto‐enol tautomerization, 1,2‐hydride shift, and internal Cannizzaro reaction) [25] . Early work has shown that the formation of MVG from C4 sugars can be stimulated by catalytic sites in confined space and operating at higher temperature [26] .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that both MLA and MVG are derived from the C3 and C4 (C2) products produced by the retro-aldol condensation of fructose and glucose, respectively, and subsequently obtained by similar chemical transformations (e.g., dehydration, keto-enol tautomerization, 1,2-hydride shift, and internal Cannizzaro reaction). [25] Early work has shown that the formation of MVG from C4 sugars can be stimulated by catalytic sites in confined space and operating at higher temperature. [26] The selectivity difference between these two products in this work, starting from glucose, may arise from the different glucose isomerization abilities of the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the notably high yield of LA could be attributed to the accessible catalytic single-sites of UiO-66 with an ability to convert the C2 residues to LA. Several efforts towards the exploration of other Zr-based materials, such as ZrO 2 , 26 metal–organic frameworks (MOFs), 27 and Zr-doped zeolites, 28 have also been devoted to selectively producing LA from xylose. However, when considering large-scale production, utilizing xylose as a platform chemical is relatively high cost compared with the more abundant and economical C6 glucose.…”
mentioning
confidence: 99%